2011 IEEE 1st International Conference on Serious Games and Applications for Health (SeGAH) 2011
DOI: 10.1109/segah.2011.6165441
|View full text |Cite
|
Sign up to set email alerts
|

Wiitherapy on seniors — Effects on physical and metal domains

Abstract: The aging population is in demand of new tools for better quality of life. Technology has this power. Aim: This study aimed to assess the impact of using Nintendo Wii® in the elderly. Methods: The impact in balance was measured using Berg scale, the activities of daily living using Barthel, cognitive status using MMSe and perceived health status using SF-36. A sample of 65 seniors from a nursing home was randomly allocated to 3 groups: Wii with the supervision of a Physiotherapist (Group A; n=23), Wii without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 20 publications
0
24
1
2
Order By: Relevance
“…Of the 29 studies that used a RCT or pre-posttest design, 21 studies included an exercise control intervention (9,13,32,33,38,43,44,47,49,53,55,57,60,64,65,67,69,72,73,80,81). The methodological quality of these 21 studies according to the PEDro classification scale is presented in Table 6.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 29 studies that used a RCT or pre-posttest design, 21 studies included an exercise control intervention (9,13,32,33,38,43,44,47,49,53,55,57,60,64,65,67,69,72,73,80,81). The methodological quality of these 21 studies according to the PEDro classification scale is presented in Table 6.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The primary aim of the reviewed studies was to evaluate the potential effect of gaming/VR exercise on balance, either alone (9,12,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), in combination with other physical abilities such as strength or mobility (11,13,(47)(48)(49)(50)(51), or in combination with falls or fear of falling, cognition, quality of life, or user experience (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Seven studies investigated the effect of gaming/VR exercise on gait parameters (63)(64)(65)(66)(67)(68)(69), and six studies examined the effectiveness with regard to different physical functions and associated fall risk (10,(70)(71)(72)…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, they developed a prototype for a new generation of gametherapies; their system represents a step forward with respect to traditional therapies as it allows for low-cost, ubiquitous exercises with the support of both instantaneous digital feedback from the application and continuous monitoring/interaction with a remote doctor. [Portela et al 2011] reported the usefulness of Nintendo Wii for improving the life and the helth of elder people. The study of [Martins et al 2011] intends to investigate the evolution of patients with intellectual disabilities using a serious game capable of monitoring their evolution, concerning memory, decision-making time, capacity of observation, learning and applying knowledge.…”
Section: Related Workmentioning
confidence: 99%